Evaluasi Program Bantuan Langsung Tunai Dana Desa (BLT-DD) Kecamatan Benakat Kabupaten Muaraenim - Dita Mayreista; Eka Nurwahyuliningsih; Mutiara Rizki (Jurnal Politik dan Pemerintahan Daerah, 2025)
This study aims to describe the results of the evaluation of the implementation of the BLT-DD program in Betung Village and its impact on the local community by focusing on the four CIPP evaluation approaches (Context, Input, Process and Product). Using a qualitative research method with a descriptive approach, with data collection techniques in the form of observation, interviews and documentation studies. Data analysis techniques use condensation, data presentation, describing and drawing conclusions. Informants in this study were taken using purposive sampling technique, namely someone who can provide information according to research needs, while the informants consisted of 8 (eight) people including the Village Head 1 person, Chairman of the BPD (Village Consultative Body) 1 person, Village Secretary 1 person, Kaur Keungan Village 1 person, People who received assistance 2 people, and People who did not receive assistance 2 people. The research location was in Betung Village, Benakat Sub-district, Muara Enim Regency. The findings in this study show that the implementation of the BLT-DD program in Betung Village has been carried out effectively in accordance with the evaluation through context, input, process, and product evaluation indicators. The BLT-DD program in Betung Village has provided significant benefits to the community affected by the pandemic, but there are still some improvements needed in several aspects, including updating beneficiary data, increasing supervision of the program, and it is hoped that in the future the BLT-DD program will be integrated with community economic empowerment programs.